TAFSIR ILMI DAN FENOMENA BIOLOGIS: MENGUAK FUNGSI PENCIPTAAN ANGIN STUDI ANALISIS TAFSIR AL JAWAHIR FI TAFSIR AL-QUR’AN AL KARIM - Lulu Alfina; Khairussalam Khairussalam; Hofifah Hofifah; Siti Hudaroh; Ani Indrawati; Andi Rosa (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2024)
Wind is a natural phenomenon involving the movement of air caused by differences in atmospheric pressure. In the interpretation of Al-Jawahir by Tanthawi Jauhari, wind is understood as a sign of Allah's greatness, with significant biological and ecological functions, such as facilitating rainfall, plant pollination, and energy distribution. This study employs a literature review method with a qualitative approach to analyze the functions of wind based on Qur'anic verses and scientific exegesis. The findings reveal that the Qur'an uses the term